The First Cut-Off Wall In The Indian Himalayas For The Dam Of The Dhauliganga Hydroelectric Project - Wolfgang G. Brunner (Deep Foundations Institute, 2004)
In the far north of Uttar Pradesh Province in the Indian Himalayas, the 280 MW Dhauliganga hydroelectric power plant is under construction by National Hydroelectric Power Corporation (NHPC), a state- owned enterprise, and a joint venture of Kajima Corporation of Tokyo and Daewoo Corporation of Seoul. This project sets out to develop the lower section of the mountain cascade of the Dhauliganga River, a tributary of the Sarda River, with a 311 m gross head. The 1360 km2 mountainous catchment area is bounded in the north- east by the Chinese border and in the south- east by the Nepalese border. The dam project is located in a remote area north of the principal town of Darchula of the upper Sarda valley, which is one of the seismically most active regions of India. The 56 m high rock fill dam, which will be the first of its kind in India, is faced with concrete and has a 1 m thick, at its crown 270 m long and over 70 m deep cut- off wall of plastic concrete below its toe. The cut- off wall, with a total area of 7500 m2, is constructed by a combination of Bauer hydraulic grabs, assisted by chisels and a Bauer BC 40 cutter which enables the overlapping joint system to be installed, guarantees optimum verticality and enables the cut- off to be keyed into the bedrock formation.